Pliocene and Pleistocene lagomorphs (Mammalia) from Northwest Africa: new discoveries - Sen, Sevket; Geraads, Denis; Pickford, Martin; Vacant, Renaud (Palaeobiodiversity and palaeoenvironments, 2024)
This work describes and interprets fossil lagomorphs from seven sites in the Maghreb the ages of which range from the Miocene/Pliocene boundary to the Upper Pleistocene. Some of these sites, such as the Thomas Quarries in Morocco and Tighennif (=Ternifine) in Algeria, are well known for the discovery of fossil humans and their artefacts. The lagomorphs studied herein belong to two families, Prolagidae and Leporidae. The genus Prolagus has been recorded in the Maghreb since the latest Miocene, c. 6.2-6.5 Ma, and its last known representatives in Africa occur at Tighennif and Djebel Ressas 5 and 6 (Tunisia) the ages of which are estimated to be between 1.0 and 1.4 Ma. In other words, this genus, which is well known in Europe since the Early Miocene, crossed the Rifian Corridor during the Messinian crisis, and became extinct in the Maghreb earlier than in southwestern Europe where it survived until historical times. Its oldest representatives in the Maghreb known from the sites of Afoud and Lissasfa (latest Miocene-Early Pliocene) are related to P. michauxi , a species that is well represented in the latest Miocene and Early Pliocene localities in southern Europe. In the Early Pleistocene of Djebel Ressas 1 (Tunisia), it is represented by a new small species, Prolagus ressasensis n. sp. Prolagus is known in Europe as an inhabitant of wooded and humid environments. But in the terminal Miocene and Plio-Pleistocene this genus was confined more particularly to the Mediterranean rim, probably as an inhabitant of open woodland, temperate regions and certainly more open than the humid and wooded environments of the Early and Middle Miocene of Europe. The Leporidae appear in the Maghreb sites around the same time as Prolagus , but in the earlier sites (Afoud and Lissasfa), they are rare and therefore their identification is imprecise (Leporidae indet. at Afoud, Trischizolagus sp. at Lissasfa). In contrast, they are abundant in terminal Pliocene and Pleistocene sites. The genus Trischizolagus , that is well documented at Ahl al Oughlam (c. 2.5-3.0 Ma) by T. meridionalis Sen and Geraads, 2023, is even more abundant in the deposits of the Casablanca region (Grotte des Rhinocéros, Thomas IL, Thomas I-GH) and in Tighennif in Algeria where it is represented by T. raynali (Geraads, 1994). The last known representatives of this genus, collected from Grotte des Rhinocéros, occur alongside the first known representatives of the genus Lepus , described here as Lepus berbericus n. sp. In the Late Pleistocene site of Thomas I, a form of Lepus similar to L. capensis is represented by numerous mandible fragments. But the systematics of this species are the subject of debate, with no consensus as to whether it is a species occurring over a wide range from South Africa to the Middle East and North Africa or whether it comprises several species of which the morphological and / or genetic features are poorly defined. The genus Trischizolagus is well known in Europe and Anatolia with several species described between 6.5 and 3.5 Ma, while it survived in the Maghreb until the Middle Pleistocene, c. 0.5 Ma. It was probably replaced by the first hares of the Maghreb, described here as L. berbericus n. sp. The extant species Lepus capensis inhabits territories with open grassland and bushland habitats. The introduction of the rabbit Oryctolagus cuniculus to the Maghreb occurred later, probably in the Late Pleistocene by prehistoric men for food.